Du système de charges aux statuts de prestige individuel - Marie Chosson (Ateliers d'Anthropologie)
The inhabitants of the Tzeltal village of Aguacatenango currently find themselves confronted with various upheavals, the most serious of which are the upcoming administrative and political reorganisation and, over the past twenty years, the diversification of religious tenets. These transformations force them to adapt or reformulate what for them constitutes “tradition” and, by extension, their identity. One of their main concerns in relation to these changes is the endangerment of their conception of good public affairs administration. Therefore, power distribution questions lie at the heart of discourse on the community’s current “modernisation” processes. This article examines their particular approach to the notion of power through an analysis of their administration’s current organisation, the system of charges. The “thick boundaries” conceptual tool makes it possible to reveal, in the margins of the system, other power spaces that are less visible but no less real to the population. This study will give us a more general view of the different spheres of power and their boundaries, subsequently enabling a simpler understanding of the real issues raised by the current changes, as well as the possible adaptation strategies that grow out of them.